Effects of extrusion ratio and direction on extruded Au nanowires investigated using molecular dynamics simulation. (5th November 2021) - Wu, Cheng-Da; Xu, Wei-Xiang
Abstract: The effects of the extrusion ratio (diameter of the extrusion mold inlet divided by that of its outlet) and direction on extruded Au nanowires (NWs) are studied using molecular dynamics simulations based on the embedded-atom method. The effects are investigated in terms of atomic trajectories, common neighbor analysis, flow field, system pressure, and the extruded NW length-pressing ram displacement curve. The simulation results show that for the forward extrusion process, a smaller extrusion ratio leads to a larger diameter of the extruded NW and a smoother cross-sectional profile. Extruded NWs obtained at a smaller extrusion ratio have a higher face-centered cubic fraction and a less disordered structure due to lower system pressure. The adhesion effect between extruded NWs and mold outer walls increases with increasing extrusion ratio, resulting in an uneven appearance of extruded NWs and a decrease in their length. The backward extrusion process can produce amorphous NWs from crystal NWs. The forward extrusion process can produce NWs that are longer than those produced with the backward extrusion process.